A case report of B lymphoblastic lymphoma with brain metastases: Clinical and pathological significance of head trauma misdiagnosis. Issue 20 (May 2018) - Shi, Jian; Manzo, Jale; Zhou, Yiwu; Agovino, Peter; Wu, Song
Abstract: Introduction: B lymphoblastic lymphoma (B-LBL) is a rare type of lymphoma that originates from precursor lymphocytes. B-BLB in adults with brain metastases is extremely rare as the disease mainly affects children and adults. Therefore, such a seldom-seen case can easily trigger a dispute regarding clinical diagnosis and treatment. This paper reports the case of a 22-year-old man hospitalized for a head injury that resulted from a physical altercation. Upon admission to the hospital, the patient was diagnosed with a diffuse axonal injury (DAI). Accordingly, the patient receiving follow-up treatments, but died 30 days later. After a systematic necropsy, immunohistochemical staining, radiological consultation, and a complete review of the clinical dates, we defined the case as a brain metastasis of B lymphoblastic lymphoma. Imaging results of the intracranial lymphoma were nearly indistinguishable from DAI during the acute phase, which led to misdiagnosis and incorrect treatment for B-LBL. Conclusion: We present this case to broaden the scope of pathologic and clinical diagnosis for intracranial tumors and to inform physicians, general neurologists, and even medical examiners with an added degree of differential awareness in dealing with the clinical materials before further diacrisis and disposal.